2003
DOI: 10.1038/sj.ejcn.1601723
|View full text |Cite
|
Sign up to set email alerts
|

Tomato consumption and plasma lycopene concentration in people aged 65 y and over in a British national survey

Abstract: Objective: Assessment of consumption of raw and processed tomatoes, plasma lycopene concentration and their interrelationship in a nationally representative sample of elderly British people. Setting: A 1994-1995 National Diet and Nutrition Survey: a nationwide cross-sectional sample of people aged 65 y and over living in mainland Britain, either in the community ('free-living', n ¼ 1275) or in institutions such as nursing homes (n ¼ 412). Methods: Consumption of raw and processed tomatoes (including those in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Therefore, in this experiment, we have optimised conditions by enriching Calu-3 cells with lycopene at a concentration of 2.5 μg/ml (that is equivalent to 4.65 μM), dissolved in 0.5% THF, for 24 h prior to exposure to RV and LPS. This amount of lycopene in the medium is almost two times higher than circulating plasma lycopene levels in healthy people, which is reported to be 0.8-1.34 μg/ml [51][52][53]. Therefore, the intracellular dose we achieved after our recommended method is likely to be biologically relevant to human physiologic systems.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, in this experiment, we have optimised conditions by enriching Calu-3 cells with lycopene at a concentration of 2.5 μg/ml (that is equivalent to 4.65 μM), dissolved in 0.5% THF, for 24 h prior to exposure to RV and LPS. This amount of lycopene in the medium is almost two times higher than circulating plasma lycopene levels in healthy people, which is reported to be 0.8-1.34 μg/ml [51][52][53]. Therefore, the intracellular dose we achieved after our recommended method is likely to be biologically relevant to human physiologic systems.…”
Section: Discussionmentioning
confidence: 62%
“…Regular consumption of tomatoes and tomato-based products has been associated with a reduced risk of chronic human diseases, such as certain cancers and cardiovascular disease [2][3][4][5]. Researchers have suggested that these beneficial health effects are attributed to their high levels of carotenoids, in particular lycopene [1,3,[5][6][7][8][9]. Tomatoes and tomato-based products are the main source of lycopene in the human diet [2,7,9], providing more than 80% of dietary lycopene [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested that these beneficial health effects are attributed to their high levels of carotenoids, in particular lycopene [1,3,[5][6][7][8][9]. Tomatoes and tomato-based products are the main source of lycopene in the human diet [2,7,9], providing more than 80% of dietary lycopene [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato lycopene is found in appreciable levels in human serum and tissues when tomatoes and tomato products are consumed frequently [139][140][141]. Several research investigations have shown an inverse relationship between plasma/serum lycopene concentrations and risk of some cancers [142][143][144][145][146][147][148].…”
Section: Tomatomentioning
confidence: 99%